ANALISIS MEKANISME PENENTUAN PROFIT MARGIN PEMBIAYAAN MURABAHAH LEMBAGA KEUANGAN SYARIAH (LKS) AL YASINI PASURUAN - Silfiyah; Muhammad Fahmul Iltiham; Abdillah Mundir (Fakultas Agama Islam Universitas Yudharta Pasuruan, 2020)
: The focus of the problem is (1) What is the mechanism for determining the selling price and profit margin in murabahah financing at Al-Yasini LKS. (2) What methods are used to determine the profit margin in murabahah financing by LKS Al-Yasini. (3) What are the factors that affect the profit margin on murabahah financing at Al-Yasini LKS. The objectives in writing this thesis have a purpose, namely: (a) To discount the selling price and profit margin on murabahah financing at LKS Al-Yasini. (b) To discuss the method in determining the selling price and profit margin carried out by LKS Al-Yasini. against murabahah financing. (c) To discuss the factors that affect the profit margin in murabahah financing at LKS Al-Yasini. This type of research is the researcher uses a qualitative approach and analysis techniques using descriptive methods by analyzing the data that has been obtained is qualitative, the sample data obtained is from primary data which is directly obtained from LKS Al-Yasini regarding the policy of determining murabahah profit margins. , and from secondary data which is processed data whose source can be trusted and scientifically accounted for by conducting literature studies, interviews, the internet, and others. The research result in this thesis is the method in determining the margin carried out by LKS Al-Yasini using themethod flat , where themethod flat is the calculation of the profit margin against the cost of cost of financing on a regular basis from one period to another, even though the debit balance decreases as a result of the installments. cost of goods sold. The factors that affect the selling price and profit margin made at Al-Yasini LKS are firstly related to the time period. second is related to the use of funds. third Related to the customer's condition.